Supramolecular Non-Amyloid Intermediates in the Early Stages of α-Synuclein Aggregation - Fauerbach, Jonathan Arturo (2012)
The aggregation of α-synuclein is associated with progression of Parkinson's disease. We have identified submicrometer supramolecular structures that mediate the early stages of the overall mechanism. The sequence of structural transformations between metastable intermediates were captured and characterized by atomic force microscopy guided by a fluorescent probe sensitive to preamyloid species. A novel ∼0.3–0.6 μm molecular assembly, denoted the acuna, nucleates, expands, and liberates fibers with distinctive segmentation and a filamentous fuzzy fringe. These fuzzy fibers serve as precursors of mature amyloid fibrils. Cryo-electron tomography resolved the acuna inner structure as a scaffold of highly condensed colloidal masses interlinked by thin beaded threads, which were perceived as fuzziness by atomic force microscopy. On the basis of the combined data, we propose a sequential mechanism comprising molecular, colloidal, and fibrillar stages linked by reactions with disparate temperature dependencies and distinct supramolecular forms. We anticipate novel diagnostic and therapeutic approaches to Parkinson's and related neurodegenerative diseases based on these new insights into the aggregation mechanism of α-synuclein and intermediates, some of which may act to cause and/or reinforce neurotoxicity.